Strategi Pemasaran Dalam Membangun Loyalitas Pelanggan Di Toko Wajit Sederhana - Hanafi, Muhammad; Gunawan, Gunawan (Peneliti.net, 2025)
The aim of this study is to analyze the marketing strategies implemented by Toko Wajit Sederhana in building customer loyalty. This research adopts a qualitative approach with data collection methods including interviews with store owners, employees, customers, and local community members, as well as direct observation at the store's premises and on its social media platforms. Data analysis involves examining several key aspects of marketing strategy, including Relationship Marketing, Customer Satisfaction, Product Quality, and After-Sales Service. The findings indicate that the integration of various marketing strategies in building customer loyalty at Toko Wajit Sederhana, including Relationship Marketing approach, customer satisfaction focus, product quality strategy, and after-sales service, has a significant positive impact. Through the Relationship Marketing approach, the store successfully strengthens personal relationships with customers and enhances emotional connections, while focusing on customer satisfaction helps maintain and expand the customer base. Consistent product quality strategies and good after-sales service also contribute to enhancing the store's brand image and maintaining long-term customer relationships. Overall, the integration of these strategies proves to be an effective step in maintaining and enhancing customer loyalty at Toko Wajit Sederhana, as well as strengthening its position in an increasingly competitive market.